Catalytic enantioselective oxidative coupling of saturated ethers with carboxylic acid derivatives - Gang Wang (Nature Portfolio, 2019)
Cross-dehydrogenative coupling (CDC) is a powerful method for C-C bond formation however the enantioselective variant is underdeveloped. Here, the authors show a formal enantioselective CDC method involving unactivated ethers and carboxylic acid derivatives allowing for the rapid preparation of biologically active molecules.